A Tinjauan Yuridis Terhadap Tindak Pidana Pencabulan Anak [Studi Kasus Putusan PN Pamekasan Nomor 8/Pid.Sus-Anak/2024/PN. Pmk] - Moh. Ali Hizam; Roesli, Muhammad (Universitas Kapuas, 2025)
Child Protection is also defined as all activities that guarantee and protect children and their rights so that they can live, grow, develop, and participate optimally in accordance with human dignity and receive protection from violence and discrimination. This study uses normative legal research by examining library materials or secondary data as a process to find legal rules, legal principles, and legal doctrines to answer the legal issues faced. The application of material criminal law in Decision Number 8/Pid.Sus-Anak/2024/PN.Pmk by the Panel of Judges uses Article 82 paragraph (1) of Law of the Republic of Indonesia No. 23 of 2002 concerning Child Protection in conjunction with Article 76E of Law of the Republic of Indonesia No. 35 of 2014 in conjunction with Article 82 of the Government Regulation in Lieu of Law No. 1 of 2016 concerning the Second Amendment to Law of the Republic of Indonesia No. 23 of 2002 as Law of the Republic of Indonesia No. 17 of 2016 concerning Government Regulation in Lieu of Law No. 1 of 2016 concerning the Second Amendment to Law No. 23 of 2002 concerning Child Protection Becoming Law is the principle of lex specialis.